ELEMENTOS VAZADOS: ANÁLISE DO DESEMPENHO LUMÍNICO - Bolssoni, Gabriela da Conceição (2021)
Solar radiation is an extremely important resource to be considered in projects as it is the main source of light and heat on the planet, thus having a direct relationship with the thermal and luminous performance of buildings. In this sense, it is worth mentioning the architectural resources perforated solar screen used to control this radiation. Thus, this research aims to evaluate the daylighting performance of perforated solar screen from the variation of different parameters for an internal office environment. In the methodology, Grasshopper + DIVA-for Rhino software was used for thermal and luminous performance evaluations and Sketchup + Vray for analysis of light and shadow visual effects. The evaluations were made for an indoor office environment located in the city of Vitória - ES (20°19'15" South latitude and 40°20'10" West longitude). Twelve closure models, one glass model and others were evaluated. models composed of glass and perforated solar screen as an external second skin, for the North, South, East and West orientations. The models were evaluated in four stages: (1) Perforated solar screen with the same thickness and different insolation angles (α ,β); (2) Perforated solar screen with the same insolation angles (α, β) and different thicknesses; (3) Perforated solar screen associated with other architectural devices (high window and light shelf); (4) Perforated solar screen associated with the light shelf with different internal depths. In the analysis of the daylighting performance, the intervals of the UDI (Useful Daylight Illuminance), the Daylighting Autonomy (DA), the Uniformity indicated by the NBR ISO/CIE were adopted as evaluation parameters 8995-1 (ABNT, 2013) and the occurrence of visual effects of light and shadow in the indoor environment. In order to complement the luminous performance analyses, the thermal performance was evaluated through the Percentage of Reduction of Solar Radiation Transmitted by the models. As main results, it was identified that the external insolation angles (α, β) are the most determining factors for daylighting of solar radiation transmitted to the indoor environment. In addition, it was found that the joint insertion of the high window and light shelves with smaller internal depths showed the ability to increase the performance of the perforated solar screen.